Burkholderia phytofirmans PsJN Confers Grapevine Resistance against Botrytis cinerea via a Direct Antimicrobial Effect Combined with a Better Resource Mobilization - Miotto-Vilanova, Lidiane; Jacquard, Cédric; Courteaux, Barbara; Wortham, Laurence; Michel, Jean; Clément, Christophe; Barka, Essaïd A.; Sanchez, Lisa (Frontiers in Plant Science, 2016)
Plant innate immunity serves as a surveillance system by providing the first line of powerful weapons to fight against pathogen attacks. Beneficial microorganisms and Microbial-Associated Molecular Patterns might act as signals to trigger this immunity. Burkholderia phytofirmans PsJN, a highly efficient plant beneficial endophytic bacterium, promotes growth in a wide variety of plants including grapevine. Further, the bacterium induces plant resistance against abiotic and biotic stresses. However, no study has deciphered triggered-mechanisms during the tripartite interaction between grapevine, B. phytofirmans PsJN and Botrytis cinerea. Herein, we showed that in contrast with classical rhizobacteria, which are restricted in the root system and act through ISR, B. phytofirmans PsJN is able to migrate until aerial part and forms at leaves surface a biofilm around B. cinerea mycelium to restrict the pathogen. Nevertheless, considering the endophytic level of PsJN in leaves, the plant protection efficacy of B. phytofirmans PsJN could not be explained solely by its direct antifungal effect. Deeper investigations showed a callose deposition, H2O2 production and primed expression of PR1, PR2, PR5 and JAZ only in bacterized-plantlets after pathogen challenge. The presence of PsJN modulated changes in leaf carbohydrate metabolism including gene expression, sugar levels and chlorophyll fluorescence imaging after Botrytis challenge. Our findings indicated that protection induced by B. phytofirmans PsJN was multifaceted and relied on a direct antifungal effect, priming of defense mechanisms as well as the mobilization of carbon sources in grapevine leaf tissues.